Translational Research in Pancreatic Cancer - Strimpakos, Alexios S; Syrigos, Konstantinos N; Saif, Muhammad W (JOP. Journal of the Pancreas, 2010)
Pancreatic cancer is an aggressive type of cancer ranking as the 10th most common cancer and the 4th cause of cancer related deaths. Due to disappointing treatment results and outcome of pancreatic cancer patients there is urgent need for better understanding of pathogenesis, mechanisms of tumor progression and resistance to treatment in order to achieve etiological approach. The development of the field of translational research and pharmacogenomics during the last several years has revealed many molecular pathways being aberrant in pancreatic cancer. This knowledge has led to the identification of biomarkers with prognostic or predictive value and the development of novel drugs against specific abnormal targets of pancreatic tumors. In this year’s ASCO Gastrointestinal Cancers Symposium, researchers presented data showing evidence of biomarkers with prognostic value (Abstracts #166, #140, and #126) and genetic polymorphisms predicting possibly efficacy of gemcitabine treatment (Abstract #166). The development of the new small molecule CRT0066101 targeting the protein kinase D (PKD), which is upregulated significantly in pancreatic cancer cells was also presented (Abstract #159). This small molecule blocked specifically PKD and inhibited potently in vitro and in vivo the growth of pancreatic cancer cells. Furthermore, a retrospective analysis of KRAS status on resected pancreatic cancer specimens showed that frequency of KRAS mutations was 67% (57% of those were on codon 12), lower than previous reported in more advanced stages (Abstract #169). In this paper we present details and comment on these works. Image: Sotiria General Hospital, University of Athens. Athens, Greece.